1911 Kan. Sess. Laws 249-50 - (:unkn) unknown (My University, 1911)
An Act Defining the Crime of Burglary With Explosives, and Providing the Punishment Therefor, §§ 1 and 2: That any person who (with intent to commit crime) breaks and enters, either by day or by night, any building, whether inhabited or not, and opens or attempts to open any vault, safe or other place by use of nitro-glycerine, dynamite, gunpowder or any other explosive, shall be deemed guilty of burglary with explosives
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME